Perilaku bullying tanpa disadari pada mahasiswa - Waluyo, Agus; Deska, Rini (JOURNAL OF Mental Health Concerns, 2025)
Baground: Unwitting bullying behavior is carried out, among others, by making physical appearance a joke, antagonizing, excluding, using harsh words and spreading news that is not factual. Purpose: To describe unconscious bullying behavior in a group of students in one of the study programs in Bandar Lampung. Method: This research was conducted descriptively quantitatively in one nursing study program with 54 students as respondents. The instrument used in this study was a questionnaire with 17 closed questions. Results: The results showed that out of 54 respondents: students who had never done bullying behavior without realizing it were 11 students (20.0%) and those who had done bullying behavior without realizing it were 43 students (80.0%). Bullying behavior in the group that has ever done is categorized into 3 groups: low category as many as 16 respondents (37.0%), medium category as many as 22 respondents (51.0%), high category as many as 5 respondents (12.0%). Conclusion: Only a small group of students have never committed bullying behavior and most of them still do it in their daily lives. Knowledge and understanding of bullying behavior or wrong words must be known by every person/individual. For this reason, each person / individual must get information and understanding about bullying behavior is behavior that should not be done. Keywords: Bullying; Students; Unconsciously. Pendahuluan: Perilaku bullying tanpa kita sadari dilakukan antara lain dengan menjadikan penampilan fisik sebagai bahan bercandaan, memusuhi, mengucilkan, penggunaan kata - kata kasar dan menyebarkan berita yg bukan fakta. Tujuan: Untuk menggambarkan perilaku bullying tanpa disadari pada kelompok mahasiswa disalah satu program studi di Bandar Lampung. Metode: Deskriptif kuantitatif pada satu program study keperawatan dengan jumlah responden sebanyak 54 mahasiswa. Instrument yang digunakan dalam penelitian ini berupa kuesioner dengan 17 pertanyaan tertutup. Hasil: Penelitian menunjukan dari 54 responden mahasiswa yang tidak pernah melakukan perilaku bullying tanpa di sadari berjumlah 11 mahasiswa (20.0%) dan yang pernah melakukan perilaku bullying tanpa disadari dengan jumlah 43 mahasiswa (80.0%). Perilaku bullying pada kelompok yang pernah melakukan dikategorikan dalam 3 kelompok kategori rendah sebanyak 16 responden (37.0%), kategori sedang sebanyak 22 responden (51.0%), kategori tinggi sebanyak 5 responden (12.0%). Simpulan: Hanya sebagian kecil kelompok mahasiswa yang tidak pernah melakukan perilaku bullying dan  sebagian besar masih melakukan dikehidupan keseharian mereka. Pengetahuan dan pemahaman tentang perilaku atau perkataan salah bersifat bullying wajib diketahui oleh setiap diri /individu. Untuk itu setiap diri/individu harus mendapatkan informasi dan pemahaman tentang perilaku bullying adalah perilaku yang tidak boleh dilakukan. Kata kunci: Bullying; Mahasiswa; Tanpa Disadari.